Investigation on the occurrence of space VLF prior to the earthquake event / Mohd Faizal Mohamed - Mohamed, Mohd Faizal (2010)
Numerous attempts have been made by geology researchers to define the relationship between some events and earthquakes, and thereby use them as an earthquake precursor tool. In recent years many publications have appeared indicating that Very Low Frequency (VLF) electromagnetic emission is recently recognized as one of the most promising candidates for short-term earthquake prediction. This project used three different data which is on 07 April 2010 at Northern Sumatera, 26 April 2010 at Taiwan, and 09 Mei 2010 at Meaulaboh. VLF data was taken from VLF receiver station that deployed a system called Atmospheric Weather Electromagnetic System for Observation Modelling and Education (AWESOME). The software used in this project is MATLAB. From the results obtained, it shows strong correlation between VLF and determination of earthquake precursors.